Analysis of Supply Chain Management Performance in the Community Coffee Production System in Bajawa, Ngada Regency - Rofinus Neto Wuli; Victoria Ayu Puspita; Igniosa Taus (Syntax Corporation Indonesia, 2023)
Research on Supply Flow Performance Management in the Bajawa People's Coffee Production System was carried out in Ngada Regency, with the aim of finding out the relationship between cooperation and the performance of the Bajawa coffee supply flow, knowing the relationship between information sharing and the supply flow performance of Bajawa coffee and knowing the long-term relationship with Bajawa coffee supply flow performance. Many factors can influence the performance of supply flow management in companies, including information sharing, long term relationships, and cooperation. The method used in this research is to analyze the relationship between the dependent variable (cooperation, information sharing and long-term relationships) and the independent variable (Bajawa coffee supply flow performance). From the results of the multiple linear regression analysis carried out, it shows that: the long-term relationship variable has the greatest influence on the Bajawa coffee SCM performance variable (dependent) with a coefficient value of (0.047), then the cooperation variable with a value of ( 0.019 ), and which has a The smallest influence is the information sharing variable (0.018). This means that the three independent variables have a positive and significant effect on the dependent variable.